Tradisi Atur Dahar Dalam Selamatan Menurut Pandangan Tokoh Agama dan Tinjauan ‘Urf : Studi di Desa Pait Kecamatan Long Ikis - Sita Andriani Padeli; Materan Materan; Akhmad Sofyan (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The Atur Dahar tradition is a ceremony to feed supernatural beings by leaving food overnight in a room, some are also drowned in the river. This tradition has become a hereditary custom by their ancestors. The existing actions are considered tabzir/wasteful and shirk. This study uses a normative empirical research type, the focus of this research is the views of religious leaders on the Atur Dahar tradition in Pait Village, Long Ikis District. The data analysis technique is carried out using a qualitative descriptive method, namely describing, explaining, and analyzing the results of the study by reviewing the study of 'urf. The procession of the Atur Dahar tradition in the celebration of the Banjar community in Pait village is divided into two implementations, namely dishes provided for ancestors, some are left overnight in the corner of the house and some are drowned in the river, but now the Atur Dahar tradition has been changed from food to which prayers are read and some have not changed, namely in the procession such as leftover food that becomes waste, and food that is less suitable or dirty is given to the community. Ten religious leaders agreed on the existence of the Atur Dahar tradition in celebrations if it complies with Islamic law. The Atur Dahar tradition is part of 'Urf Amali' because it is an act carried out by the community, especially the Banjar tribe in Pait village. This tradition is included in 'Urf Khash' because it is a custom of the Banjar tribe in Pait village. In terms of law, it is included in 'Urf Sahih', because some of the procession is in accordance with Islamic law, such as praying to Allah SWT and sharing food as alms with others. This tradition can also be included in 'Urf Fasid' because it is wasteful.